One grid to rule them all. (Economist, 2004)
This article describes the efforts of physicists and engineers to develop a worldwide computing network so effective that it acts as one computer. The stated goal of grid computing is to create a network of computers interconnected so well and so fast that they act as one. Yet most of the time, this over-hyped catchphrase is used to describe rather mundane improvements that allow companies to manage their workload more flexibly by tapping into idle time on their computers. At a meeting on computing in high-energy physics held in late September 2004 in Interlaken, Switzerland, physicists and engineers reviewed progress towards an altogether more ambitious type of computing grid, which aims to create a truly seamless system. Physicists' demand for computing power is being spurred by the flood of data that will pour out of the Large Hadron Collider (LHC), the next-generation particle smasher due to start operation in 2007 at CERN, the European particle physics laboratory near Geneva. The decision to build a distributed computing system to deal with this deluge of data predates the hype about grid technology and is purely pragmatic: it would be difficult to fund the necessary computational power and storage capacity if it were concentrated on one site. If, on the other hand, the computations are distributed among the hundreds of institutes worldwide that are involved in the LHC, each institute can tap into national or regional funding sources to raise cash, spreading the pain. The LHC Computing Grid (LCG) started providing a bare-bones service to high-energy physicists a year ago, with at first just 12 centres involved. The LCG project has rapidly ironed out the worst problems, and now involves some 80 computing centres in 25 countries contributing over 7,000 computers. This is still far short of the requirements of the LHC, but with three years to go before the collider is ready, prospects for narrowing the gap look good.